2013
DOI: 10.1245/s10434-013-3200-6
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Dissection Can Be Avoided in the Majority of Clinically Node-Negative Patients Undergoing Breast-Conserving Therapy

Abstract: Background or Purpose The extent to which ACOSOG Z0011 findings are applicable to patients undergoing breast-conserving therapy (BCT) is uncertain. We prospectively assessed how often axillary dissection (ALND) was avoided in an unselected, consecutive patient cohort meeting Z0011 eligibility criteria and whether subgroups requiring ALND could be identified preoperatively. Methods Patients with cT1,2cN0 breast cancer undergoing BCT were managed without ALND for metastases in <3 sentinel nodes (SNs) and no gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 29 publications
4
71
0
3
Order By: Relevance
“…Dengel et al, 17 in a prospective study designed to determine how often ALND can be avoided in patients meeting ACOSOG Z0011 eligibility criteria, reported that 84% of patients, not selected on the basis of age, tumor characteristics, axillary imaging, or nomogram predictions, were found to have metastases in 2 axillary nodes, thus suggesting that these patients had a low axillary tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…Dengel et al, 17 in a prospective study designed to determine how often ALND can be avoided in patients meeting ACOSOG Z0011 eligibility criteria, reported that 84% of patients, not selected on the basis of age, tumor characteristics, axillary imaging, or nomogram predictions, were found to have metastases in 2 axillary nodes, thus suggesting that these patients had a low axillary tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of patients with more than 2 positive SLN will add valuable evidence to clinical practice, since these patients were excluded from Z0011. A prospective study of a consecutive cohort of patients who met the Z0011 criteria at the time of initial surgery at the Memorial Sloan-Kettering Cancer Center showed that 29 of 287 patients (10.1%) underwent completion ALND for ≥3 positive SLNs [24.] On the other hand, the randomization of patients with isolated tumor cells or micrometastases into the ALND arm is nowadays considered overtreatment by many, at the latest since the publication of IBCSG 23-01 [9.]…”
Section: Ongoing Randomized Controlled Trialsmentioning
confidence: 99%
“…Этот вывод применим независимо от характеристик опухоли, таких как дольковый гистотип рака, обширный внутрипротоковый компонент, молодой возраст или неблагоприятный биологический подтип [6]. Как было показано в ряде крупных исследований, у женщин с опухолями T1-2 и клинически негативны-ми ЛУ (cN0) отказ от подмышечной лимфаденэктомии при наличии макрометастазов в 1 или 2 ЛУ [30,31] оказался безопасным [32]. В большом популяционном исследовании в США, включавшем более 200 тыс.…”
Section: хирургическое лечениеunclassified